Correction: Association of birth weight, childhood obesity, and age at menarche with the risk of ovarian dysfunction: A mendelian randomization study. - Chunxiao Dang; Jianjuan Li; Xiao Yu; Jinxing Liu; Pengfei Liu; Xiaoling Yang (PLoS ONE, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0306365.].